How does QI work? A trust-building framework in African healthcare: primary evidence from Kenya and Malawi - Mary B Adam; Kedar Mate; Naomi Wambui Makobu; Tod Newman; Angela Joy Donelson (BMJ Open Quality)
Trust is fundamental to the effective functioning of healthcare systems, influencing access, utilisation and adherence to evidence-based practices. While quality improvement (QI) processes are widely recognised for addressing technical challenges, their role in fostering trust and relationships within health systems remains underexplored. This study examines the relationship dynamics in QI teams and how trust-building frameworks align with adaptive processes in healthcare settings. We conducted a qualitative study involving 30 healthcare workers from six African countries, recruited through the Africa Consortium for Quality Improvement in Frontline Healthcare. Data were collected through semistructured interviews, transcribed and analysed using both inductive and deductive methods. Deductive analysis was guided by a published trust-building framework, while insights from a large language model were incorporated in addition to a traditional analysis to provide an unbiased perspective. Results identified three theoretically described dimensions of trust-building within QI teams: common goals, self-interest and gratitude/indebtedness. Common goals fostered teamwork, multidisciplinary collaboration and effective communication, while self-interest motivated personal and professional growth. Gratitude and recognition reinforced team cohesion and sustained motivation. Participants highlighted the importance of trust in achieving project success, noting that robust relationships within teams correlated with improved outcomes. The study underscores the dual nature of QI processes, which simultaneously address technical improvements and adaptive challenges, including trust and relationship-building. Trust-building, framed as an iterative process of aligning common goals, recognising contributions and addressing individual interests, complements technical QI methodologies like Plan-Do-Study-Act cycles. These findings support expanding QI frameworks to emphasise relational dynamics, contributing to more sustainable and impactful healthcare improvements. Further research should continue to explore the adaptive dimensions of QI, integrating recent research on culturally relevant frameworks prioritising kindness in healthcare systems, to enhance trust and collaboration within healthcare systems.